Measuring the Health Impact of Drinking Water Sources in El-Fashir, Sudan (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed to assess the physical and chemical condition of drinking water in El-fashir city, Sudan. Theparameters studied are; Electrical conductivity (EC), nitrates, pH, Total Dissolved Solid (TDS) and fluorinewere analyzed at water points and in the laboratory. Results were processed on SPSS software. The studyrevealed the pH results, which were distributed between 6.8 to 8 for samples from hand pumps 1 and 2 andtank water, respectively. The residual chlorine concentration (RC) in the water supply system of the selectedstations ranged between 0.2 to 0.6 mg /L. The concentration of nitrate level ranged from 3. 4.5 mg/L, whichis within the acceptable range of the standards for WHO and SSMO standards. The study also determinedthe level of fluorine, which ranged between 0.17 - 0.41 mg/L, which is within the acceptable range of thestandards for WHO and SSMO standards. This study found that all results fall within the permissible limitsof the standards of WHO and SSMO standards except the hand pumps.